Remote Learning Challenges during the Covid-19 Pandemic - Meisya Qurrata A’yun; Ulfatuz Zahiroh Meysa; Tyasmiarni Citrawati (UIN Raden Mas Said Surakarta, 2022)
Technological advancements in the 21st century have rendered humans inseparable from technology. This situation demands that the school sector, notably in Indonesia, adjust to the changes that occur, particularly concerning the Covid-19 outbreak. The government shifted education to remote learning. This study discusses the difficulties encountered by teachers and students during remote learning caused by the Covid-19 pandemic. It describes how to overcome these challenges, as well as what needs to be prepared to implement remote learning. It also determines which applications may be used to facilitate remote learning. Interviews and observation were used for data collection. From a teacher and six first-grade students at SD Negeri Pakong 2, it was revealed that challenges experienced by teachers and students were in terms of difficulties in improving student learning outcomes, lack of gadgets, unstable internet connections, as well as unaffordable internet quota. Alternative solutions suggested in this study are conducting IT training, home visits, and proposing internet quota to the government. The recommended applications to overcome these problems are WhatsApp and Google Classroom.